Risk factors associated with asbestos-related lung diseases among different sub-cohorts of formerly asbestos exposed workers in Germany. (19th October 2011) - Khatab, Khaled; Felten, Michael; Kandala, Ngianga-Bakwin; Ghilagaber, Gebrenegus; Kraus, Thomas
Abstract : Objectives: To examine the association between work-place exposure to asbestos and risk factors for developing asbestos related diseases using the analysis of a cross-sectional cohort of 8582 formerly asbestos exposed workers followed between March 2002 until the end of the year 2009. To assess the value of the three risk categories used for focused health surveillance programmes among formerly asbestos exposed power industry. Methods: The work started with a descriptive analysis of three asbestos exposed sub-cohorts of workers from different types of the power industry then assessed the difference between the three sub-cohorts with regard to their corresponding level of risk. Further, we investigated how well the risk categories could predict the risk of asbestos related disease in comparison to applying a single risk factor such as age or asbestos exposure. Results: The smokers over 65 age of years and those who had an exposure duration over 10 years were more likely to have lung cancer in this cohort. Hence the results showed that the age of participants (over 65 years, OR=11.47), smoking habits (OR=9.48 (current smoker), were associated significantly with lung cancer. The results showed that the risk of having lung cancer in group A was 1.87 times. Conclusions: There was a strong association between both duration of exposure and age, and the risk of developing lung cancer. The use of risk categories based on a combination of risk factors may be an advantage for planning focused health surveillance programmes.